Natural gamma-ray spectroscopy (NGS) as a proxy for the distribution of clay minerals and bitumen in the Cretaceous McMurray Formation, Alberta, Canada. (15th March 2021) - Day-Stirrat, Ruarri J.; Hillier, Stephen; Nikitin, Anton; Hofmann, Ronny; Mahood, Robert; Mertens, Gilles
Abstract: Detailed examination of the mineralogy of the Cretaceous McMurray Formation within a facies framework is used to assess the use of natural gamma-ray spectroscopy (NGS) and a pulsed neutron generator (PNG) tool in delineating variation in clay mineral and bitumen contents. Characterization of the mixed-layer (interstratified) clay phases in the McMurray Formation provides an improved understanding of clay interaction in bitumen processing and tailings settling behavior, important for mine planning and tailings remediation schemes. Mineral diversity in the McMurray Formation was determined on facies attributed samples using whole rock X-ray diffraction (XRD), cation exchange capacity (CEC) measurements, elemental analysis (XRF), clay size fraction (<2 µm) XRD analysis, reflected light microscopy, and cryogenic-scanning electron microscopy (cryo-SEM). Kaolinite was ubiquitous in the entire McMurray Formation with lower and middle McMurray Formation sediments also containing mixed-layered illite–smectite (I-S) with a low expandability≈ 20–30%. Upper McMurray Formation sediments by contrast had higher expandability (≈ 60–70%). In floodplain sediments of the lower McMurray Formation an additional clay mineral was quantified as a kaolinite-expandable mixed-layer (clay) mineral. The associated CEC values of this mineral are 10 times the baseline for the McMurray Formation. NGS spectra from cores showed that yields of potassium (K), uranium (U), and thorium (Th) had distinct facies associations, correlated with a clay mineral signature. The resultant indicator is capable of highlighting zones within an oil sands ore body that are empirically known, by industry, to process poorly through extraction plants. A bitumen indicator from the carbon yield derived from a PNG logging tool assesses bitumen content. NGS and PNG allow a full assessment of clay mineral (fines) and bitumen profiles, with the future prospect that these techniques could be used to assess ore and tailings behavior in near-real time.